In Vitro and In Situ Degradation Characteristics and Rumen Fermentation Products of Moringa oleifera Harvested at Three Different Ages - A. R. Seradj; H. Morazan; M. Fondevila; J. B. Liang; G. De la Fuente; J. Balcells (Tropical Animal Science Journal, 2019)
Besides the beneficial agronomic properties such as drought tolerance and high biomass production, the high crude protein content of Moringa oleifera (Moringa) makes it comparable to the other high quality forages. This study aimed to evaluate whether Moringa can be an appropriate substitute for alfalfa as a ruminant feed. The study consisted of 4 treatments, namely Moringa leaves harvested at 30 (M30), 40 (M40), and 50 (M50) days after pruning, and alfalfa (Medicago sativa) hay as a control. Simultaneously, their organic matter digestibilities and fermentation characteristics were analyzed by in vitro gas production technique and rumen dry matter and protein degradability kinetics were analyzed by using the nylon bags (in situ) procedure. The results of in vitro study revealed that the potential cumulative gas production for Moringa sample harvested at 30 days after pruning was higher than that of alfalfa while the rate of gas production and the concentrations of ammonia and volatile fatty acids (VFA) in Moringa were similar to alfalfa. Moringa harvested at different times had higher in vitro organic matter digestibility (IVOMD) and metabolizable energy (ME) content as compared with alfalfa. Despite the apparent higher soluble fraction (a) and the fractional degradation rate (c) in the Moringa samples of various ages than those for alfalfa, the differences were not significant. However, in situ potentially degradable fraction (b) for DM and CP of Moringa harvested at different ages were higher than those of alfalfa (P<0.05). The in vitro fermentation and in situ degradation parameters suggested high similarities in the kinetics of gas production (i.e. a, b, and c) and DM degradation pattern among the three different cutting ages of Moringa and nutritionally they were comparable to alfalfa. In conclusion, alfalfa could be replaced with Moringa leaves in diet of ruminant animal without any adverse effect.